Desarrollo de un material para la fabricación de tacones con residuos de madera (2017)
The present project is realized with the objective of giving an integral use to the wood from the residues generated during its cutting and molding, developing a material that fulfills the required properties to be used as raw material in the manufacture of heels for shoes Of women currently manufactured in ABS (Acrylonitrile butadiene styrene), which are bought at the Lisantiny shoe factory, taking advantage of the sawdust, which in the MADERAS LA 170 deposit does not represent any kind of benefit, obtaining higher added value products In another sector and contributing to the conservation of the environment.